Struktur dan Perkecambahan Serbuk Sari Pada Porang (Amorphophallus Muelleri Blume) - Dwi Gusmalawati; Serafinah Indriyani; Rodiyati Azrianingsih; Zainal Abidin (Universitas Islam Raden Rahmat, Malang, 2023)
This study aims to analyze the structure and germination of pollen in porang. Pollen structure and germination were observed microscopically. Pollen germination observations were carried out three days before anthesis (M-3), two days before anthesis (M-2), one day before anthesis (M-1), anthesis (M) to four days after anthesis (M+4). Pollen in porang has a dimorphic structure (X and Y structures: monad and compound units). Structure X with axis length (P)= 30-50 µm, equatorial diameter (E)= 16.67-41.67 µm, and index P/E= 1.19-1.79, while structure Y with P= 50-84 µm, E= 34-67 µm, and P/E index= 1.25-1.40. Porang pollen was subspheroidal and prolate in shape; the length of the axes of the media and magna types; monocolpate aperture type. The highest viability of the X structure was at M (31.58%), while the Y structure was at M+1 (21.76%). M+3 viability begins to decline, so porang artificial pollination is appropriate when pollen viability is high (M or not more than M+3).